Educação popular e educação escolar quilombola: entre concepções, desafios e possibilidades no contexto da Escola Municipal Quilombola Professora Antônia do Socorro Silva Machado - Cunha, Heloísa Marinho (2025)
This study investigates the interface between Popular Education from a Freirean perspective and Quilombola School Education, based on the paradigm of Afrocentricity. It argues that this interlocution contributes to reflection on the National Curriculum Guidelines for Quilombola School Education (DCNEEQ) and can enhance their implementation at the Professora Antônia do Socorro Silva Machado Quilombola Municipal School (EMQASSM), in Paratibe, João Pessoa-PB. The objectives of the study include identifying the contributions of Afro-Brazilian civilizational values and Freirean categories in the construction of the quilombola curriculum, discussing the perception of educational leaders and professionals about the school-community relationship, analyzing the implementation of African and quilombola know-how in everyday school life and evaluating the challenges and advances in the implementation of Afrocentered and Popular Education. The research adopts a qualitative approach, using bibliographical, documentary and field research. For data collection, a field diary, participant observation, questionnaires and semi-structured interviews with community leaders and EMQASSM teachers were used. The data was analyzed using Critical Discourse Analysis (CDA) from the perspective of Norman Fairclough (2016). The results reveal that Quilombola School Education in Paratibe faces advances and setbacks, due to low teacher engagement and the prevalence of pedagogical practices limited to commemorative dates of Afro-descendant culture. The conclusion is that the implementation of quilombola education depends not only on teacher training, but also on the commitment of the João Pessoa Municipal Department of Education and Culture (SEDEC-JP) and dialog with the quilombola community. This study seeks to contribute to the construction of a public school that values the knowledge, traditions and ways of life of historically invisible groups, promoting a more inclusive and representative curriculum.